Innovative Learning Strategies by Embedding Design Thinking-based Project Learning in Textbooks for Edupreneurial Impact - Yunita, Sri; Gandamana, Apiek; Lubis, Wildansyah; Rachman, Fazli; Bali, Sandrotua (Aptisi Transactions On Technopreneurship (ATT), 2025)
The research aims to develop a textbook that integrates design thinking to optimize project-based learning. The article presents the results of integration feasibility and effectiveness tests design thinking to optimize the project-based learning process. The research aims to provide a textbook that supports project-based learning design thinking to fulfill the content, process, and means of learning. R&D was carried out by adopting the Thiagarajan Four-D model for the MKWK for Citizenship Education at Universitas Negeri Medan. Data was collected by observation, document study, literature study, questionnaires, and tests. Development results in textbook-based design thinking to optimize project-based learning is declared feasible. This conclusion was confirmed after validating linguistic, media, and material aspects, and was declared valid because the V index value (V ≥ 0.61). Textbook-based design thinking is considered practical by lecturers and students, the V index value is greater (V ≥ 0.61). Implementation of textbook-based design thinking, which has been developed, affects student learning outcomes based on the paired t-test producing a significance value of p = 0.000 (sig. 0.000 < 0.05). This significance value confirms the significant positive (meaningful) influence textbooks on student learning outcomes after intervention or treatment and does not happen by chance.